“ELF-aware teacher education and development. - Nicos Sifakis; Yasemin Bayyurt (J. Jenkins, W. Baker & M. Dewey (Eds.), The Routledge handbook on English as a Lingua Franca., 2017)
Developments in ELF research in the past several years have raised implications for many different domains surrounding the use, teaching and learning of English involving non-native speakers. What this research has offered is a fresh way of looking at English-medium communications that include non-native users, raising serious implications about the nature of the very notion of ‘English’ (Jenkins et al., 2011; Seidlhofer, 2011, p. 105; Widdowson, 1997). In this chapter, we focus on implications of ELF research for teacher education. As ELT situations around the world abound, we put forward the notion of ELF-aware teacher learning and development (our term) and suggest ways in which it can impact teacher development through appropriate teacher education. To that end, we present a framework for teacher education programmes aiming to raise teachers’ ELF awareness.